2008
DOI: 10.1002/jcb.21960
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a transgenic yeast screening system for estrogenicity and identification of the anti‐estrogenic activity of malachite green

Abstract: Endocrine disruptors refer to chemical compounds in the environment which interfere with the endocrine systems of organisms. Among them, environmental estrogens pose serious problems to aquatic organisms, in particular fish. It is therefore important and necessary to have a fast and low-cost system to screen the large number of different chemical compounds in the aquatic environment for their potential endocrine disrupting actions. In this study, a screening platform was developed to detect xenoestrogens in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…It has been shown that MG at 1 ppm is able to reduce the growth of different fungal species, such as Aspergillus parasiticus, Aspergillus flavus, Penicillium verrucosum, and Fusarium oxysporum (5). MG also is used in the fish industry to treat fungal and ectoparasitic diseases in eggs (22,44). We show here that MG has an advantage over conventional antifungal drugs in that it effectively inhibits the growth of C. albicans and non-C. albicans species at lower concentrations than those of triazoles, imidazoles, and allylamine.…”
mentioning
confidence: 99%
“…It has been shown that MG at 1 ppm is able to reduce the growth of different fungal species, such as Aspergillus parasiticus, Aspergillus flavus, Penicillium verrucosum, and Fusarium oxysporum (5). MG also is used in the fish industry to treat fungal and ectoparasitic diseases in eggs (22,44). We show here that MG has an advantage over conventional antifungal drugs in that it effectively inhibits the growth of C. albicans and non-C. albicans species at lower concentrations than those of triazoles, imidazoles, and allylamine.…”
mentioning
confidence: 99%
“…Further, after 3 -5 days of incubation, it was unknown if any oxidation reactions were occurring that may activate the target compound. Some newer colorimetric assays have dramatically shortened the time required for color development (4-6 h) through the use of alternative substrates but have the disadvantage of requiring cell lysis steps (Jaio et al, 2008). To overcome these limitations, bioluminescent version of the YES and YAS reporters were developed by modifying the plasmid constructs of Gupta et al (2003).…”
Section: Chemical Detection Using S Cerevisiae-based Bioluminescent mentioning
confidence: 99%
“…Naringenin, the aglycone of the candidate substance naringin .058], has been tested for estrogenic effects in a number of in vitro screening test studies with different end-points (Almstrup et al, 2002;Bovee et al, 2008;Bovee et al, 2004;Branham et al, 2002;Breinholt & Larsen, 1998;Galluzzo et al, 2008;Garrett et al, 1999;Jiao et al, 2008;Kretzschmar et al, 2009;Kuiper et al, 1998;van Meeuwen et al, 2007;Miksicek, 1993;Rosenberg Zand et al, 2000;Safe et al, 2002;Zierau et al, 2005;Zierau et al, 2003;Zierau et al, 2002). Generally it is concluded that naringenin is a weak in vitro estrogen compared to isoflavone phytoestrogens like genistein.…”
Section: Naringeninmentioning
confidence: 99%